MEMBANGUN KARAKTER GENERASI MUDA MELALUI PENDIDIKAN INFORMAL, FORMAL, DAN NONFORMAL - Nuriah Hanifah; Arin Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
Character is the behavioral values expressed by humans based on religious norms, laws, manners, culture and customs related to God Almighty, oneself, fellow human beings, the environment and the nation, which are manifested in thoughts, attitudes, feelings , words and deeds. The purpose of this research is to find out how to build the character of the younger generation through education and character building in the family, school and community. The research method uses a literature review. From the results and discussion, it can be concluded that to build the character of the nation's young generation, education and character building are needed. Education and character building not only come from formal education (school), but also from informal education (family) and non-formal education (community). Character education must be designed and implemented systematically and simultaneously to help students understand the values of human behavior that relate to themselves, fellow human beings, the environment and God. As cultured beings, humans must have a commitment to character or morality that is upheld. In character education, behavior, character or morality must not only be inherited but must also be applied in everyday human life. In this regard, character education is needed for the younger generation.